Expression of angiogenesis associated matrix metalloproteinases and extracellular matrix proteins in cerebral vascular malformations - (:unkn) unknown (ELSEVIER SCI LTD, 2010)
This study aimed to compare cerebral arteriovenous malformations (AVM) and cerebral cavernous malformations (CCM) with regard to the immunohistochemical expressions of matrix metalloproteinases (MMP) and selected extracellular matrix (ECM) proteins, which have a role in the regulation of angiogenesis. Fresh-frozen surgical specimens from patients with AVM (n = 14) and CCM (n = 15) were immunohistochemically stained with antibodies for MMP-2, MMP-9, laminin, fibronectin and tenascin. To compare AVM and CCM, expression of each protein was graded using a four-point scoring system for each histological layer of the lesion. MMP-2 and MMP-9 were more strongly expressed in the vascular walls of CCMs compared to AVMs for all comparable layers: endothelium, subendothelium and the perivascular space. The stronger expression of MMP and other ECM proteins associated with early angiogenesis in CCMs compared to AVMs may support the hypothesis that CCMs occur at an earlier embryogenic stage than AVMs. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Angiogenesis; Cerebral arteriovenous malformation; Cerebral cavernous malformation; Fibronectin; Laminin; Matrix metalloproteinase; Tenascin; CENTRAL-NERVOUS-SYSTEM; HUMAN CEREBROVASCULAR MALFORMATIONS; BRAIN ARTERIOVENOUS-MALFORMATIONS; CAVERNOUS MALFORMATIONS; STRUCTURAL PROTEINS; MECHANISMS; TENASCIN; COLLAGEN; RECEPTOR; LAMININ